COMPRESSIVE STRENGTH OF SOLID ROUND STEEL MEMBERS REINFORCED WITH SPLIT PIPE(S) - Cindy Kumalasari; Vrushali M. Tickle; Murty K.S. Madugula (Civil Engineering Dimension, 2005)
Results of experimental investigation on the compressive strength of twenty solid round steel leg member specimens of lattice communication towers reinforced with one or two split pipe(s) are presented in this paper. The reinforcement was connected to the leg members either by means of U-bolts only or by means of U-bolts and end welding. It was found that bolt torque has no significant effect in the increase on the strength. It was also concluded that using two split pipes without end welding is better than using one split pipe with end welding. Based on the test results, a simplified and conservative design procedure in accordance to the Canadian and American Standards is proposed to determine the compressive strength of solid round steel leg members reinforced with split pipe(s).